PENGARUH PENGGUNAAN APLIKASI QUIZIZZ DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM TERHADAP MOTIVASI BELAJAR SISWA DI KELAS VII MTS SALAFIYAH SYAFI’IYAH TEBUIRENG JOMBANG (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discusses the effect of using the Quizizz application in Islamic Cultural History learning on students’ learning motivation at MTs. Salafiyah Syafi’iyah Tebuireng Jombang. The background of this study is the low level of students’ learning motivation in Islamic Cultural History learning. Therefore, innovative learning media that are interesting, interactive, and in line with technological developments are needed, one of which is the use of the Quizizz application.The objectives of this study are: (1) to determine whether the use of the Quizizz application affects students’ learning motivation at MTs. Salafiyah Syafi’iyah Tebuireng Jombang; (2) to describe the level of students’ learning motivation in Islamic Cultural History learning at MTs. Salafiyah Syafi’iyah Tebuireng Jombang; and (3) to analyze the effect of the use of the Quizizz application on students’ learning motivation in Islamic Cultural History learning at MTs. Salafiyah Syafi’iyah Tebuireng Jombang.This study employed a quantitative approach. The research was conducted at MTs. Salafiyah Syafi’iyah Tebuireng Jombang. The population of this study consisted of all seventh-grade students, while the sample was selected using the Stratified Cluster Sampling technique. Data were collected through questionnaires, and the data were analyzed using SPSS for Windows with simple linear regression analysis. The results of the study show that: (1) the use of the Quizizz application in Islamic Cultural History learning is categorized as moderate, as indicated by the highest distribution of respondents’ answers in the “undecided” category, totaling 19 students (35.1%); (2) the level of students’ learning motivation is also categorized as moderate, indicated by the highest distribution of respondents’ answers in the “undecided” category, totaling 20 students (36.9%); and (3) there is a significant effect of the use of the Quizizz application in Islamic Cultural History learning on students’ learning motivation of seventh-grade students at MTs. Salafiyah Syafi’iyah Tebuireng Jombang. This is evidenced by the t-test results (significance value of 0.000 < 0.05 and t-count of 4.249 > t-table of 1.67469), indicating that the alternative hypothesis is accepted and the null hypothesis (H₀) is rejected.